2009
DOI: 10.3858/emm.2009.41.6.045
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate inhibits adipocyte hypertrophy and insulin resistance by activating adipose PPARα in high fat diet-induced obese mice

Abstract: Peroxisome proliferator-activated receptor α (PPARα) activation in rodents is thought to improve insulin sensitivity by decreasing ectopic lipids in non-adipose tissues. Fenofibrate, a lipid-modifying agent that acts as a PPARα agonist, may prevent adipocyte hypertrophy and insulin resistance by increasing intracellular lipolysis from adipose tissue. Consistent with this hypothesis, fenofibrate decreased visceral fat mass and adipocyte size in high fat diet-fed obese mice, and concomitantly increased the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 46 publications
8
77
0
Order By: Relevance
“…These data raised the possibility that an enhanced BAT thermogenesis could be an underlying cause of the increase in energy expenditure induced by Z-551. Since there are reports to the effect that PPAR␣ agonists increase fatty acid combustion in the liver and promote lipid degradation in the adipose tissue (11,15), and PPAR␥ antagonists show anti-obesity effects (24,25), we consider that both PPAR␣ agonistic and PPAR␥ antagonistic activities of Z-551 contribute to the anti-obesity effects. In fact, the effects, of Z-551 in PPAR␣-deficient mice and CZD-2 in WT mice suggest that the anti-obesity effects of Z-551 are not only due to the PPAR␣ activation but also due to the PPAR␥ inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data raised the possibility that an enhanced BAT thermogenesis could be an underlying cause of the increase in energy expenditure induced by Z-551. Since there are reports to the effect that PPAR␣ agonists increase fatty acid combustion in the liver and promote lipid degradation in the adipose tissue (11,15), and PPAR␥ antagonists show anti-obesity effects (24,25), we consider that both PPAR␣ agonistic and PPAR␥ antagonistic activities of Z-551 contribute to the anti-obesity effects. In fact, the effects, of Z-551 in PPAR␣-deficient mice and CZD-2 in WT mice suggest that the anti-obesity effects of Z-551 are not only due to the PPAR␣ activation but also due to the PPAR␥ inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␣ is mainly expressed in the liver, and plays wide-ranging roles in lipid metabolism, energy homeo-stasis, and inflammation (9,10). Fibrates, PPAR␣ agonists, and drugs for dyslipidemia promote peroxisomal and mitochondrial ␤-oxidation, and inhibit fatty acid synthesis in the liver due to activation of PPAR␣, resulting in amelioration of insulin resistance owing to decreased ectopic fat accumulation in peripheral tissues (11)(12)(13)(14)(15). On the other hand, PPAR␥ has two isoforms, PPAR␥1 and PPAR␥2 formed by selective splicing.…”
mentioning
confidence: 99%
“…PPAR ␣ activators regulate obesity by increasing hepatic fatty acid oxidation and decreasing the levels of the circulating triglycerides responsible for adipose cell hypertrophy and hyperplasia (42)(43)(44); PPAR ␥ activators induce adipocyte gene expression and improve insulin sensitivity ( 11,45 ); and, PPAR ␦ activators induce fatty acid oxidation in skeletal muscle ( 46 ) and activate glucose transport in myotubes ( 36 ). Our analyses of the effects of 8-HEPE in FaO, 3T3-F442A, and C2C12 cells showed that it induced expression of genes known to be regulated by PPAR ␣ ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Large adipocytes increase the levels of circulating free fatty acids, tumor necrosis factor α, and leptin, which are associated with insulin resistance (Okuno et al, 1998;Jeong and Yoon, 2009;Oh et al, 2015). Therefore, GE and testosterone may alleviate metabolic disease by inhibiting adipocyte hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ginseng has been suggested to reduce weight gain in animal models of obesity and can effectively regulate genes involved in obesity (Attele et al, 2002;Kim et al, 2005;Karu et al, 2007;Mollah et al, 2009;Lee et al, 2009Lee et al, , 2012. Ginseng also significantly inhibits visceral obesity and adipocyte hypertrophy (Lee et al, , 2014, which is closely associated with metabolic syndromes (Okuno et al, 1998;Jeong and Yoon, 2009;Lee et al, 2014). In this study, we examined the effects of Korean red ginseng extract (GE) and/or testosterone on obesity and adipogenesis in high-fat diet (HFD)-fed castrated C57BL/6J mice and 3T3-L1 adipocytes.…”
Section: Introductionmentioning
confidence: 99%